Determinants of Online Shopping and Moderating Role of Innovativeness and Perceived Risk - Rizwan, Muhammad; Sultan, Hamna; Parveen, Sadia; Nawaz, Shumaila; Sattar, Samreen; Sana, Maryam (Asian Journal of Empirical Research, 2013)
Time and trend wait for none. We are no more in Stone Age. It is 2012, Glass Age, where time is money, so better skips the malls and start online shopping. The basis of this revision is to discover the influence of different variables on future intention of online shopping and the perception of people about online shopping as how people perceive shopping via internet by using technology. This research offers insight into the consumer’s attitude. The outcomes have very significant effects on sellers, marketers and system providers of online shopping. A questionnaire survey has been carried out to test the hypothesis. The sample of 150 respondents is collected through a questionnaire. The hypotheses are tested by regression analysis. The outcomes show that attitude is an effective variable which has positively strong effect on future intention of online shopping even though the perceived usefulness and perceived ease of use affects attitude to online shopping. Innovativeness has a substantial progressive impact on future intention of online shopping. Many studies on online shopping determine the impact of technology on it, yet this study determines the effect of attitude on online shopping.